PENGARUH PROMOSI, DESAIN PRODUK DAN KESADARAN MEREK TERHADAP KEPUTUSAN KONSUMEN UNTUK MEMBELI MOBIL TOYOTA YARIS - Raden Ayu Widaningsih; Handoyo Djoko Waluyo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2014)
The purpose of this study is to determine how much influence promotion, product design and brand awareness to the consumer's decision to buy a Toyota Yaris in Nasmoco Pemuda Semarang. The sample is the consumer brand of car owners and users who purchased the Toyota Yaris in PT. Nasmoco Pemuda Semarang. A total of 85 respondents using purposive sampling technique. From the results of the study partially through t-test showed that there is a positive and significant effect between the variables promotion, product design and brand awareness of the Toyota Yaris car purchasing decisions in Nasmoco Pemuda Semarang. Then based on the research results simultaneously through f test that there is a positive and significant effect of the variable promotion, product design and brand awareness of the Toyota Yaris car purchasing decisions in Nasmoco Pemuda Semarang. Variable promotion, product design and brand awareness to the purchasing decision a Toyota Yaris in Nasmoco Youth of 35.6 percent.